2016
DOI: 10.3897/mycokeys.14.9729
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of microsatellite markers in the cosmopolitan lichen-forming fungus Rhizoplaca melanophthalma (Lecanoraceae)

Abstract: Rhizoplaca melanophthalma s.l. is a group of morphologically distinct and chemically diverse species that commonly occur in desert, steppe and montane habitats worldwide. In this study, we developed microsatellite markers to facilitate studies of genetic diversity, population structure, and gene flow in the nominal taxon of this group, Rhizoplaca melanophthalma. We characterized 10 microsatellite markers using a draft genome of R. melanophthalma s. str. assembled from Illumina reads. These loci were tested for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…While highly detailed, these studies of lichen population genetics represent only a fraction of this diverse group of fungi that have evolved an obligate symbiotic lifestyle at least seven times independently throughout the fungal tree of life (Schoch et al 2009), and occupy every terrestrial ecosystem from the poles to the tropics (Brodo et al 2001). Microsatellites have recently been developed for a broader diversity of lichenized fungi (Magain et al 2010; Devkota et al 2014; Nadyeina et al 2014; Lindgren et al 2016; Lutsak et al 2016), however these tools have not yet been utilized for population genetic analyses in lichens.…”
Section: Introductionmentioning
confidence: 99%
“…While highly detailed, these studies of lichen population genetics represent only a fraction of this diverse group of fungi that have evolved an obligate symbiotic lifestyle at least seven times independently throughout the fungal tree of life (Schoch et al 2009), and occupy every terrestrial ecosystem from the poles to the tropics (Brodo et al 2001). Microsatellites have recently been developed for a broader diversity of lichenized fungi (Magain et al 2010; Devkota et al 2014; Nadyeina et al 2014; Lindgren et al 2016; Lutsak et al 2016), however these tools have not yet been utilized for population genetic analyses in lichens.…”
Section: Introductionmentioning
confidence: 99%
“…While highly detailed, these studies of lichen population genetics represent only a fraction of this diverse group of fungi, which have evolved symbiotic relationships with algae or cyanobacteria at least seven times independently throughout the fungal tree of life (Schoch et al., ) and occupy every terrestrial ecosystem from the poles to the tropics (Brodo et al., ). Microsatellites have recently been developed for a broader diversity of lichenized fungi (Magain et al., ; Devkota et al., ; Nadyeina et al., ; Lindgren et al., ; Lutsak et al., ), but these tools have not yet been utilized for population genetic analyses in lichens.…”
mentioning
confidence: 99%
“…In such cases, a temporal framework may help to distinguish between species and populations within species ( Leavitt et al, 2016a ). Although the use of microsatellites has become popular in population studies of lichen-forming fungi (e.g., Lindgren et al, 2016 ), next-generation sequencing [NGS] technologies have been shown to produce higher amounts of information across the whole genome to be used in population studies of lichen-forming fungi ( Divakar and Crespo, 2015 ;Werth et al, 2015 ;Dal Grande et al, 2017 ). Genotyping by sequencing methods ( Narum et al, 2013 ;Andrews et al, 2016 ), including restriction-site associated DNA sequencing (RAD-seq; Baird et al, 2008 ), represent cost-eff ective means that allow a more accurate approach to delve into population structure, including questions on the stochasticity of lineage sorting, the genetic footprint of the founder eff ect, and the eff ects of natural selection and genetic drift on isolated populations ( Jeff ery et al, 2017 ;Narum et al, 2017 ).…”
Section: Future Perspectives In the Study Of Bipolar Lichensmentioning
confidence: 99%